A report on diversity and distribution of macrofungi in the Garhwal Himalaya, Uttarakhand, India - Semwal, Kamal C.; Bhatt, Vinod K. (Biodiversity: Research and Conservation, 2019)
We report mycodiversity of the different forest types of the Garhwal Himalaya, Uttarakhand, India. The results drawn here are based on the study carried out in the different forest sites of the Garhwal Himalaya during the rainy season from 2013 to 2015. We collected a total of 323 specimens, including 310 specimens belonging to Basidiomycota and 13 to Ascomycota. Furthermore, 212 specimens of Basidiomycota were identified and grouped into 33 families, 75 genera and 198 species, while 13 specimens of Ascomycota were grouped into 7 families, 7 genera and 11 species. 127 species were found in oak dominated temperate broadleaved forest, while 42 were collected from coniferous and 19 from the mixed woodland composed mainly of Quercus, Myrica, Rhododendron and Pinus trees in middle to higher hills, and Shorea robusta and Tectona grandis in the dipterocarp forests of lower hills. In terms of fungal species distribution in these forests, Amanitaceae, Russulaceae and Boletaceae were found most dominant in oak dominated forests, whereas Tricholomataceae and Cantharellaceae were commonly found in Pinus and Cedrus dominated forests and those belonging to family Cortinariaceae – in mixed forests. Species belonging to the families Agaricaceae, Amanitaceae and Tricholomataceae were found dominant in dipterocarp forest in the lower Himalayan region. The majority of species belonging to all families were found near lower to mid range altitude, which may result from the overlapping effect of atmospheric temperature and climate. The members of seven families, i.e., Russulaceae, Amanitaceae, Tricholomataceae, Boletaceae, Cantharellaceae, Cortinariaceae and Gomphaceae, were found as main ectomycorrhizal forming species from the elevation range of 500-2800 m a.s.l., in all four forest types.